The gendering of programmers’ work: taking China’s IT industry as an example - Xiaotian Li (The Journal of Chinese Sociology)
Abstract This paper discusses the gendering of programmers’ work in China at both the occupational and work organization levels: the dichotomy between social and technical aspects in programming work leads to a gendered hierarchical division of labor that undermines the legitimacy of women programmers’ professional identities. Additionally, the combination of the overtime culture in technology companies and traditional gender role expectations makes women more likely to face work‒family conflicts. This paper uses the concept of embodiment to analyze women’s experiences of exclusion and women’s motivation to reconcile their gender and occupational identities and plan their career development. Thus, it simultaneously reveals how gender rules operate and how they may be changed in programming work.